TECHNOLOGIES OF TEACHING ELEMENTARY SCHOOL STUDENTS TO EXPRESSIVE READING OF WORKS OF ART (Scientific journal of the Fergana State University, 2023)
Instilling a love for books and reading in primary school students, familiarizing children's hearts with books is considered as one of the urgent issues. By reading works of art, children learn good and bad, black and white, learns to distinguish between high and low. His love for goodness increases and he hates evil. At this point, there are also specific types and directions of artistic works, based on the age characteristics of primary school students, suitable for them and choosing specific works and teaching them to read correctly, accurately, fluently also requires high pedagogical skills from the pedagogue. Reading a book, first of all, shapes the students' imagination. Each of our actions and thoughts is based on a certain idea. In order for something, an event, an object to become an event, it must first pass through our imagination. That is, the reality without our imagination is an abstraction. The most important aspect of life is that what a student imagines, he can achieve. Human imagination creates reality. Geniuses who made great discoveries in history were great people who had more than their imagination. The reader's imagination works in the process of reading a book. He imagines the distant past and the future. He embodies the life of his contemporaries in his imagination. This process takes place not in the form of a lifeless picture on the TV screen, but in the mind of the reader, in the world of imagination. And by itself, it is able to make changes in the mind of the student. Therefore, this article is about teaching children to read works of art with love and to read consciously and expressively.